An optimized design of in-shoe heel lifts reduces plantar pressure of healthy males - Zhang, Xianyi; Li, Bo; Liang, Kaiyun; Wan, Qiufeng; Vanwanseele, Benedicte (Gait & posture, 2016)
•An optimized heel lift design with an arch support was introduced.•The optimized heel lift reduced heel pressure without increasing forefoot pressure.•The arch support used in this study did not put additional load on the midfoot. Conventional heel lift with a flat surface increases the risk of foot problems related to higher plantar pressure and decreased stability. In this study, an optimized design of in-shoe heel lifts developed to maintain the midfoot function was tested to investigate if the plantar pressure distribution was improved. The design was based on three dimensional foot plantar contour which was captured by an Infoot 3D scanning system while the heel was elevated by a heel wedge. To facilitate midfoot function, an arch support was designed to support the lateral longitudinal arch, while allowing functional movement of the medial longitudinal arch. Twenty healthy male subjects were asked to walk along an 8m walkway while wearing high-cut footwear with and without the optimized heel lift. Peak pressure, contact area and force–time integral were measured using the Pedar insole system. Range and velocity of medial-lateral center of pressure during forefoot contact phase and foot flat phase were collected using a Footscan pressure plate. Compared to the shoe only condition, peak pressure under the rearfoot decreased with the optimized heel lift, while no increase of peak pressure was observed under the forefoot and midfoot regions, indicating improved plantar pressure distribution. The findings of this study suggest that this optimized heel lift has better biomechanical performance than a conventional flat heel lift. Results from this study may have implications for insole and shoe last design, especially for people who need additional heel height without sacrificing midfoot function.